Strategic Evaluation and Selection for Energy-Effective Natural Fibers as Alternative Sustainable Insulation Materials for Green Building Envelope - Balo, Figen; Sua, Lutfu S. (CRC Press, 2023)
The use of traditional insulation materials has four primary effects on the ecology: natural resource consumption, energy usage, greenhouse gaseous emissions, and massive waste production. Plant-based insulation materials, as an alternative, offer significant benefits in terms of health and the environment. Insulation is the main element of green building design. The use of insulation materials containing natural fiber is an important step toward sustainable, environment-friendly, and effective insulation materials. This chapter intends to explore natural fiber-based insulation materials in building envelope, their advantages over traditional materials, and the challenges and opportunities in relation to their use. The focus of this study is the selection of the most effective natural fiber among others that can be used in the production of natural material-sourced insulation materials for buildings. For this purpose, an analysis was made using the AHP methodology, which is one of the multi-criteria decision-making methods. © 2023 selection and editorial matter, Ajay, Parveen, Sharif Ahmad, Jyotsna Sharma, Victor Gambhir.